The electron beam dynamics simulation in the laser-electron storage ring involving Compton and intrabeam scattering - Gladkikh, P.I.; Karnaukhov, I.M.; Telegin, Yu.N.; Zelinsky, A.Yu. (Вопросы атомной науки и техники, 2002)
The feasibility of the development of intense X-ray sources based on Compton scattering in laser-electron storage rings is discussed. The results of the electron beam dynamics simulation involving Compton and intrabeam scattering are presented.